Regional Diversity of Buddhist Heritage Tourism in South Asia and Southeast Asia - Kiran Shinde (Heritage)
This paper examines the regional diversity in Buddhist heritage and its use for tourism in Asia, more specifically, South Asia and Southeast Asia. Based on an analysis of secondary sources and data from national tourism organisations, it illustrates inter-regional and intra-regional aspects of tourism related to Buddhist heritage. It is found that in spite of their archaeological nature, Buddhist sites in South Asia are converging points for Buddhist tourism, as these are directly related to the Buddha, and many international Buddhist monasteries enliven them with transnational Buddhist practice. Whereas in Southeast Asia, Buddhism is more of a cultural landscape that pervades from the village-level practice of Buddhism to monumental places dedicated to Buddha, which collectively form a major resource for cultural tourism. This paper argues that regional connections and religious and cultural similarities of Buddhist heritage in countries of Southeast Asia contribute to the cultural distinctiveness in the Asian paradigm that can foster sustainable development of tourism in the region.